Students' Attitude Towards Interactive Demonstration Methods in Physical Education - Shrestha, Madhav Kumar (Educational Journal, 2024)
This study was carried out to analyze the students' attitude towards interactive demonstration methods in physical education. The necessary information was taken from the eleven-community secondary school’s students of the Kathmandu Valley. This study was based on descriptive research design. The majority of the responses were found to be associated with the statement that disagrees and strongly disagrees. The range of disagreeing and strongly disagree responses was 20.8-42.8% for the statement of sports skills test. These were all together 73.3% as the strong responses out of 120 students. It was found that the student has slightly negative responses towards the statements of sports skill test. Similarly, the chi-square value was 53.58, 103.0, 100.2, 75.86 and 90.16 respectively. The p-value for all statements was 0.000 which was less than that of the 0.05 level of significance with the degree of freedom 4. This indicated that there was a significant difference between the observed scores and the expected scores of the respondents.